Kajian Nilai dalam Upacara Rajaswala - Ida Ayu Dwidyaniti Wira (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The Rajaswala ceremony is one of the yadnya ceremonies carried out by parents with the hope that the child is aware of his physical and psychological growth. For Hindus, this ceremony is a model of self-control and preventing unwanted things. The process of the Rajaswala Ceremony is essentially a ngayab ceremony like Sabuh Rah because in other Manusa Yad ceremonies there is no such thing as Sabuh Rah's ngayab ceremony. The process of the Rajaswala ceremony contains the intention of a human effort to purify a child who is just increasing adolescence, for children who are experiencing menstruation for the first time. The meaning and purpose of the Rajaswala Ceremony is also related to the meaning and function of the Manusa Yadnya ceremony, which is to purify and nurture and educate humans both physically and mentally.